Green Economy and Sustainable Development - Zhironkin, Sergey; Cehlar, Michal (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Considering the importance of the challenges for sustainable development, this Book is intended to disseminate the results of cutting-edge research and broadcast the opinions of scientists from around the world, providing technological breakthroughs in green energy and urbanism, recycling and modernization of basic industries, conducting fundamental research on the economic problems of the transition to sustainable development.